Reuse of a residue from petrochemical industry with portland cement (2012)
In this article we study the possibility of using a residue from the petrochemical industry, as a partial replacement of Portland cement, evaluating the presence of contaminants in the residue and its encapsulation, once it has been confined with the cement. The foregoing, in order to determine whether its use as a building material, may or may not cause a negative effect on the environment. The residue, called catalyst used for catalytic cracking (FCC), is a material that is composed of a type Y zeolite, dispersed in a matrix of inorganic oxides. The TCLP technique (of Toxicity Characteristic Leaching Procedure), in mortars added with 20%, of FCC with respect to the amount of cement was applied. The results showed that the catalyst does not represent a problem from the point of view of the leaching of elements, such as As, Pb, Zn, Cr and La, which were below the permissible limits. Additionally, the pozzolanic activity of the FCC was evaluated, from ASTM C311, where the effectiveness of the residue as a cementitious addition is demonstrated. With the results, the importance of reusing a waste from the petrochemical industry is highlighted, which in addition to reducing the amount of cement to be used, improves the mechanical strength of the materials that contain it.